Efficacy and safety of electrochemotherapy combined with peritumoral IL‐12 gene electrotransfer of canine mast cell tumours. (3rd February 2016) - Cemazar, M.; Ambrozic Avgustin, J.; Pavlin, D.; Sersa, G.; Poli, A.; Krhac Levacic, A.; Tesic, N.; Lampreht Tratar, U.; Rak, M.; Tozon, N.
Abstract: Electrochemotherapy combined with peritumoral interleukin‐12 (IL‐12) gene electrotransfer was used for treatment of mast cell tumours in 18 client‐owned dogs. Local tumour control, recurrence rate, as well as safety of combined therapy were evaluated. One month after the therapy, no side effects were recorded and good local tumour control was observed with high complete responses rate which even increased during the observation period to 72%. IL‐12 gene electrotransfer resulted in 78% of patients with detectable serum IFN‐γ and/or IL‐12 levels. In the treated tumours vascular changes as well as minimal T‐lymphocytes infiltration was observed. After 1 week, the plasmid DNA was not detected intra‐ or peritumorally and no horizontal gene transfer was observed. In summary, our study demonstrates high antitumour efficacy of electrochemotherapy combined with IL‐12 electrotransfer, which also prevented recurrences or distant metastases, as well as its safety and feasibility in treatment of canine mast cell tumours.